Unmethylated Vitamin D Receptor (VDR) pada Multi Drug Resistant Tuberculosis - Sibuea, Christine Verawaty; Sinaga, Janry; Zega, Elsa Bea Nibasi; Zebua, Restin Julianti; Batee, Selvian (Nommensen Journal of Medicine, 2023)
ABSTRACT Background : Cases of Tuberculosis (TB) and multi-drug resistant Tuberculosis (MDR TB) caused by mycobacterium tuberculosis are high globally. Vitamin D has an important role against TB infection by inducing antimicrobial peptides such as cathelicidin through vitamin D receptors (VDR). Several studies suggest that there is a genetic influence for TB infection, such as polymorphism and methylation. Methylation of VDR gene is one of the causes of susceptibility to TB infection. Objective : This study aimed to describe the unmethylated vitamin D receptor gene in patients with MDR TB and pulmonary non-MDR TB in Medan City. Methods : This research was a descriptive studied with a cross sectional research design. Stored DNA sample isolated from blood 40 patient MDR TB blood and 40 patient non MDR TB was converted to bisulfite with EZ DNA Methylation-Gold Kit. Converted DNA was amplified by PCR and finally gel electrophoresis was performed with agarose gel to see the unmethylated. Results : Unmethylated VDR gene was higher in MDR TB (17,5%) than in non MDR TB (null). Unmethylated VDR gene was found higher in men (15%) and in age 18-49 (10%). Conclusion : There was no unmethylated VDR gene in non MDR TB. The unmethylated VDR gene was found in MDR TB. Keywords : MDR TB, VDR gene, unmethylated ABSTRAK Latar belakang : Tuberkulosis (TB) dan multi drug resistant tuberculosis (MDR TB) yang disebabkan oleh mycobacterium tuberculosis sangat tinggi kasusnya secara global. Vitamin D mempunyai peran penting melawan infeksi TB dengan menginduksi peptida antimikroba seperti cathelicidin melalui vitamin D receptor (VDR). Beberapa penelitian menyebutkan adanya pengaruh genetik dalam terinfeksi TB paru yaitu polimorfisme dan metilasi. Metilasi gen VDR menjadi salah satu penyebab kerentanan terinfeksi TB paru. Tujuan : Penelitian ini bertujuan untuk mengetahui gambaran unmethylated gen VDR pada penderita MDR TB dan non MDR TB di Kota Medan. Metode : Penelitian ini merupakan penelitian deskriptif kategori dengan rancangan penelitian cross sectional. Sampel DNA tersimpan yang diisolasi dari darah 40 penderita MDR dan 40 penderita non MDR TB dikonversi menjadi bisulfit dengan EZ DNA Methylation-Gold Kit. DNA yang terkonversi diamplifikasi dengan PCR dilakukan elektroforesis gel dengan gel agarosa untuk melihat metilasi. Hasil : Unmethylated gen VDR lebih banyak pada MDR TB (15%) daripada non MDR TB (0). Unmethylated gen VDR lebih banyak ditemukan pada laki-laki (15%) dan pada usia 18-49 tahun (10%). Kesimpulan : Tidak terdapat unmethylated gen VDR pada non MDR TB. Unmethylated gen VDR ditemukan pada MDR TB. Kata Kunci : MDR TB, gen VDR, unmethylated